Letter to the Unknown Indian Kisan - Kandikuppa, Sandeep; Gupta, Pallavi (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
This letter is an expression of gratitude, from two students of social movements in India who are currently working in the USA, to the thousands of unknown Indian kisans (peasants). In 2020-21, peasants from across the country protested and participated in a movement widely known as anti-farm law movement—which was, in turn, triggered by the passage of three laws, together known as the farm laws, that aimed to liberalize agricultural commodity production and marketing. But what started out as a movement with a limited purpose soon morphed into a statement against the high-handedness of the Indian state. Through this letter, we pay a tribute to the farmers who drew inspiration from diverse intellectual strands including Gandhiism and Ambedkarite philosophy to craft a profound statement to highlight the precarity experienced by the farmers and in defense of India’s democratic ethos.